Impacts of BIM policy on the technological progress in the Architecture, Engineering, and Construction (AEC) industry: evidence from China - Yonghong Chen; Yufan Yang; Lan Luo; Chenyongjun Ding (Journal of Asian Architecture and Building Engineering)
Building Information Modeling (BIM) technology is increasingly crucial in the digital transformation of the Architecture, Engineering, and Construction (AEC) industry. Evaluating the effectiveness of BIM technology policies is essential for advancing the industry’s digital innovation. A quasi-natural experiment was conducted using panel data from 30 provinces in China between 2007 and 2017 to analyze the impact of BIM technology policy on the AEC industry’s technological progress from the perspective of innovation diffusion. The technological change index (TCH) of each province was calculated using the DEA-Malmquist model. The impact of BIM technology policy on technological progress in the AEC industry was analyzed using a time-varying difference-in-differences (DID) approach. The study found that BIM technology policy significantly affects technological progress in the AEC industry. The mediating effect model shows that the influence path of “BIM policy →BIM technology innovation diffusion → technological progress” is verified. The impact of policies on technological progress varies in different regions, and the higher the level of development of a region, the more it can benefit from BIM technology policies. This paper aims to share China’s experience for BIM policy formulation and implementation, and provide suggestions for promoting the high-quality development of the international AEC industry.